2020
DOI: 10.3389/fnbeh.2020.596919
|View full text |Cite
|
Sign up to set email alerts
|

Resilience: Safety in the Aftermath of Traumatic Stressor Experiences

Abstract: The relationship between adverse experiences and the emergence of pathology has often focused on characteristics of the stressor or of the individual (stressor appraisals, coping strategies). These features are thought to influence multiple biological processes that favor the development of mental and physical illnesses. Less often has attention focused on the aftermath of traumatic experiences, and the importance of safety and reassurance that is necessary for longer-term well-being. In some cases (e.g., post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 207 publications
0
12
0
1
Order By: Relevance
“…First, in studies that evaluate healthcare professionals, our findings revealed that spiritual and religious issues are important aspects for these professionals and can influence their health and clinical practice. Some articles have emphasized that the mental health of professionals has been affected by the pandemic and identified spirituality and good family functioning (Kim et al, 2021 ), as well as religious or spiritual beliefs and practices (Sierra Leguía & Montalvo Prieto, 2012 ) and faith (Matheson et al, 2020 ) as coping strategies. This is fully supported by previous studies before the pandemic, which have also found that religiosity and spirituality were significantly associated with a reduction in anxiety levels and an improvement in depressive symptoms (Gonçalves et al, 2015 ; Hook et al, 2010 ; Peselow et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, in studies that evaluate healthcare professionals, our findings revealed that spiritual and religious issues are important aspects for these professionals and can influence their health and clinical practice. Some articles have emphasized that the mental health of professionals has been affected by the pandemic and identified spirituality and good family functioning (Kim et al, 2021 ), as well as religious or spiritual beliefs and practices (Sierra Leguía & Montalvo Prieto, 2012 ) and faith (Matheson et al, 2020 ) as coping strategies. This is fully supported by previous studies before the pandemic, which have also found that religiosity and spirituality were significantly associated with a reduction in anxiety levels and an improvement in depressive symptoms (Gonçalves et al, 2015 ; Hook et al, 2010 ; Peselow et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite early traumatic experiences that most participants experienced, participants exhibited remarkable resiliency that allowed them to turn their lives around toward a path of recovery and healing. Resiliency provides positive adaptations regardless of previous negative and traumatic experiences (Matheson et al., 2020). This post‐traumatic growth (Jayawickreme & Blackie, 2014) proved to be the turning point for many participants, altering their lives positively, lends itself to resilience and skill development needed to survive in the world as they get older.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore suggested that these cultural, spiritual, and existential aspects of individuals seeking refuge and asylum, should be formulated, and explored as part of culturally informed care. More research is needed into the therapeutic nature of these protective factors and strengths, which can support resilience and recovery in the aftermath of migration related trauma experienced by these vulnerable individuals (Lusk et al, 2021;Matheson et al, 2020).…”
Section: Cultural Spiritual and Existential Supportmentioning
confidence: 99%